PENGARUH PENGGUNAAN KAPUR SEBAGAI BAHAN PENGISI (FILLER) TERHADAP KARAKTERISTIK CAMPURAN BETON ASPAL LAPIS AUS (AC- WC) - Andri Andri; Arief Setiawan; Novita Pradani (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Increased population growth boosted road transport infrastructure. So it takes a good pavement structure. Efforts to increase the hot asphalt mix with the new specification implies the use of hydrated lime as an anti stripping agent in the mix asphalt. This study aimed to investigate the characteristics of the use of hydrated lime as a filler that uses a mixture of asphalt with aggregate filler composition arrangement between a stone dust and hydrated lime on Asphaltic Concrete - Wearing Course (AC - WC). The composition is lime: stone dust is 0%: 100%, 25%: 75%, 50%: 50%, and 75%: 25%.  The results of this research indicate that the lime filler significantly affects the quality of the mix, the value of stability, flexibility, durability, density, VIM, VMA, VFB, and flow with the value of F table greather than F arithmetic based on Anova two factor analysis. From the research lime used 0%, 25%, and 50%, due to the variation of 75% lime can not set the value of the optimum bitumen content. Stability values obtained at optimum bitumen content in lime variation of 0%, 25% and 50% is 1114,862 kg, 1243,425 kg, and 1167,645 kg. And for Retained Marshall Stability value of 94,303%, 98.301% and 99.202%. The quality of the mix with hydrayed lime as a filler is better. Based on the value of Marshall Stability and durability, it can be stated that the addition of hydrated lime as a filler can improve the quality of the mix. Keyword: Lime, filler, Asphaltic Concrete - Wearing Course(AC-WC)